Postoperative water and electrolyte disturbances after extended endoscopic endonasal transsphenoidal surgery - Canelo Moreno, Juan Manuel; Dios Fuentes, Elena; Venegas Moreno, Eva; Remón Ruíz, Pablo Jesús; Muñoz Gómez, Cristina; Piñar Gutiérrez, Ana; Cárdenas Valdepeñas, Eugenio; Kaen, Ariel; Soto Moreno, Alfonso (Frontiers in Endocrinology, 2022)
Introduction: Water and electrolyte disturbances are common after pituitary surgery and can generally be classified into transient hypotonic polyuria and transient or permanent diabetes insipidus (DI). The prevalence varies in the literature between 31-51% for transient hypotonic polyuria, 5.1-25.2% for transient DI, and 1-8.8% for permanent DI. Objective: The aim of this study was to identify the prevalence of water and electrolyte disturbances with polyuria and the preoperative and postoperative predictive factors in patients undergoing surgery with an extended endoscopic endonasal approach. Material and methods: This retrospective observational descriptive study included 203 patients with a diagnosis of pituitary adenoma who underwent their first transsphenoidal surgery via the extended endoscopic endonasal approach between April 2013 and February 2020. The diagnosis of water and electrolyte disturbances was based on the criterion for polyuria (>4 ml/kg/h). Postoperative polyuria was defined as those cases diagnosed during the immediate postsurgical period that resolved prior to discharge. Transient DI included all cases with a duration of less than 6 months but still present at hospital discharge, and permanent DI included cases lasting more than 6 months. Results: The overall prevalence of water and electrolyte disorders was 30.5% (62), and the prevalence of postoperative polyuria was 23.6% (48). The median number of desmopressin doses administered to patients with postoperative polyuria was one dose (interquartile range [IQR] 1-2), and thus the median duration of treatment was 0 days. The median initiation of desmopressin was the second day after surgery (IQR 1-2). The overall prevalence of DI was 6.89%. Among the patients with transient DI, the duration was less than 3 months in three patients (1.47%), and between 3 and 6 months in two (0.98%). Nine patients had permanent DI (4.43%). (4.43%). Conclusions: The prevalence of electrolyte disturbances in our study was high, although similar to that found in the literature. Most of the cases were transient hypotonic polyuria that resolved within one day. The prevalence of transient DI in our cohort was lower than that described in the literature, while permanent DI was similar.